2014
DOI: 10.3389/fphar.2014.00256
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor drugs and neuronal plasticity in reward and aversion: focus on the ventral tegmental area

Abstract: GABAA receptors are the main fast inhibitory neurotransmitter receptors in the mammalian brain, and targets for many clinically important drugs widely used in the treatment of anxiety disorders, insomnia and in anesthesia. Nonetheless, there are significant risks associated with the long-term use of these drugs particularly related to development of tolerance and addiction. Addictive mechanisms of GABAA receptor drugs are poorly known, but recent findings suggest that those drugs may induce aberrant neuroadapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 150 publications
(183 reference statements)
1
21
0
Order By: Relevance
“…Plasticity of inhibitory transmission on VTA GABA neurons can modify the pharmacological action of addictive drugs that target GABA A R (Vashchinkina et al, 2014). In agreement with previous studies (O'Brien and White, 1987;Tan et al, 2010), our findings show that positive modulation of GABA A R signaling by diazepam attenuates VTA GABA neuron activity in drug naïve animals.…”
Section: Discussionsupporting
confidence: 92%
“…Plasticity of inhibitory transmission on VTA GABA neurons can modify the pharmacological action of addictive drugs that target GABA A R (Vashchinkina et al, 2014). In agreement with previous studies (O'Brien and White, 1987;Tan et al, 2010), our findings show that positive modulation of GABA A R signaling by diazepam attenuates VTA GABA neuron activity in drug naïve animals.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, preclinical work has shown that activation of µ‐opioid receptors is also required for the acute rewarding and reinforcing effects of drugs. Other neurotransmitter systems, including serotonin (5‐hydroxytryptamine, 5‐HT) and gamma‐aminobutyric acid (GABA), are believed to contribute to the binge/intoxication stage by modulating DA and opioid systems.…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 99%
“…The NAc sends GABAergic inhibitory projections to dopaminergic neurons of the VTA [ 19 , 20 ]. VTA has reciprocal projections with many forebrain structures including the NAc, dorsal striatum, amygdala, and mPFC [ 21 ]. Two major subdivisions of the mPFC, IL and the PL, send direct projections to the VTA [ 22 ].…”
Section: Anatomical Connectivity Between the Hippocampus And Pfcmentioning
confidence: 99%